Growth And Yield Of Tomato Plants(Lycopersicum esculentum Mill) Servo F1 Varieties Due To Application Of Soil Soil Destruction (Novelgro Terra) And Reduction Of Npk Fertilizer Dosage - alwi hasan; Agus Sugianto; Mahayu Woro Lestari (AGRONISMA, 2022)
Researchto find out the influence of soil-fixing applications that are expected to facilitate the availability of nutrients, and soil quality so as to reduce the amount of inorganic fertilizer use and improving the quality of tomato plant production. This research was conducted on the land area of Merjosari Village of Malang City and Integrated Laboratory of the Faculty of Agriculture, Universitas Islam Malang. The study was conducted on 01 Maret until August 1, 2021. The research design used is a Factorial Randomized Group Design (RAK) consisting of two factors, with 12 treatments and 3 repeats. The results showed that the parameters of the plant's height, the number of leaves, the area of the leaves at the age of 28 hst had a noticeable effect. In the yield of soil-fixing plants of 0.5 ml / liter of water was able to reduce the use of NPK fertilizer by 50% on variable fruit set yields of 59.72% and the number of harvested fruit with a value of 19.58 pieces/ton. At harvest weight, the treatment of K1P3 (bio-soil destruction 0.5 ml / liter of water + NPK fertilizer 50%) is able to increase by 17.28 tons / ha.